Academic Self-concept in University Students: Their Association with Parents' Educational Level and Previous Experience in Higher Education - Relmu Gedda Munoz; Natalia Villagrán Del Picò (LED Edizioni Universitarie, 2020)
The aim of this research is to associate academic self-concept with the educational level of the parents and previous experiences of students in higher education. It is a cross-sectional study that evaluated 1093 students from a private university in Chile. The instruments used were the academic self-concept scale (ASCS), the variables of educational level of the parents and students previous experience in higher education. Bivariate correlations were made using the Spearman coefficient, associations using Pearson's Chi-Square, and mean difference using the Mann-Whitney U between ASCS with the parents' educational level and previous experience in higher education. The outcomes indicate correlation, association and mean difference (p < .05) between the ASCS and the educational level of the mother when she has university studies, as well as with the existence of previous experiences in higher education, being the father's educational level of no significant impact. In conclusion, academic self-concept is greater when students have a mother with university studies and when they have previous experiences in higher education.